Using molecular approaches to assess rabies virus diversity in Haiti and the Dominican Republic - Condori, Rene E.; Dilius, Augustin Pierre; Cadet, Rolain; Lopez-Nuñez, Griselda; Diaz-Mateo, Elinna; Gomez-Belliard, Anna K.; Ross, Yasmeen B.; Boutelle, Cassandra; Velasco-Villa, Andres; Gigante, Crystal M.; Li, Yu; Wallace, Ryan M. (Frontiers in Microbiology, 2026)
Hispaniola, comprised of Haiti and the Dominican Republic, is a rabies-endemic island. Since 2013, Haiti and the Dominican Republic have operated advanced surveillance systems that have increased the number of humans and animals tested. In this study, rabies-positive samples collected between 2014 and 2023 were sequenced. Phylogenetic analysis revealed that the rabies virus (RABV) from Hispaniola forms a novel ‘Caribbean subclade’ with two distinct lineages: a major lineage associated with dogs and found across Haiti and parts of the Dominican Republic and a second lineage associated with dogs and mongoose found only in the Dominican Republic. Phylogenetic data support dogs as the main rabies reservoir in Haiti and show evidence of cross-border transmission. In the eastern part of the Dominican Republic, the evidence supports mongooses as the primary reservoir of rabies. Subclades within Haiti suggest that geospatial segregation of dogs and rabies may offer opportunities for zoned rabies elimination programs.